2006
DOI: 10.2216/05-29.1
|View full text |Cite
|
Sign up to set email alerts
|

A novel, simplified technique for preservation and rapid isolation of total RNA from the toxic dinoflagellateAlexandrium catenella(Dinophyceae)

Abstract: HALLEGRAEFF. 2006. A novel, simplified technique for preservation and rapid isolation of total RNA from the toxic dinoflagellate Alexandrium catenella (Dinophyceae). Phycologia 45: 311-318.A simple and rapid protocol for isolating high-quality RNA from the neurotoxic dinoflagellate Alexandrium catenella is described. We compare the use of fresh cells, preserved cells and different treatments of cell homogenisation on RNA yield and quality. Alexandrium catenella is an ideal model species for difficult-to-lyse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Several cell disruption methods have been tested (bead beating, grinding using a micropestle and sonication) against dinoflagellates Alexandrium catenella [46]. Cell disruption using micropestle were reported the most efficient method to disrupt the dinoflagellates cells.…”
Section: Isolation Of Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…Several cell disruption methods have been tested (bead beating, grinding using a micropestle and sonication) against dinoflagellates Alexandrium catenella [46]. Cell disruption using micropestle were reported the most efficient method to disrupt the dinoflagellates cells.…”
Section: Isolation Of Rnamentioning
confidence: 99%
“…However, a recent report demonstrated that mRNA degradation may occur rapidly with some genes start to degrade as early as 2 min [76]. Utilizing RNA stabilization solution such as RNAlater and RNAlater ICE seems effective to stop the dinoflagellates gene expression without compromising RNA integrity [46].…”
Section: Challenges and Consideration In Dinoflagellates Transcriptommentioning
confidence: 99%
“…2). Various approaches for cell homogenizations were tested here as previously used for different dinoflagellate species such as vortexing (Lin et al 2002), micropestle (Harlow et al 2006), or glass beads (Takishita et al 2003). Interestingly, the highest yield was obtained when applying vigorous cell homogenization with glass beads using the bead beater at a speed of 4,500 rpm for 1.5 to 6 min ( Table 2).…”
Section: Rna Extraction and Rna Qualitymentioning
confidence: 99%
“…), total RNA was isolated using TriReagent (Karako-Lampert et al 2006), then Stratagene RNA RT-PCR Miniprep kit and glass beads for homogenization step (Takishita et al 2003) or Qiagen RNeasy Plant Mini-kit (Takahashi et al 2008). In toxic dinoflagellate Alexandrium catenella, RNA isolation was carried out using Qiagen column-based RNeasy Plant Minikit and cell disruption by grinding in a micropestle (Harlow et al 2006). Consequently, the objectives of this work were to evaluate various RNA extraction methods with respect to RNA recovery and RNA quality and to explore their use in downstream applications such as complementary DNA (cDNA) synthesis, reverse transcriptase polymerase chain reaction (RT-PCR) and qPCR.…”
Section: Introductionmentioning
confidence: 99%
“…This supersaturated ammonium sulfate solution has been shown to adequately preserve both RNA and DNA for lengthy periods of time (from 6 weeks to 4 months) in a variety of animal tissues as well as whole, relatively small organisms, such as arachnids (Vink et al 2005), bacteria (Bachoon et al 2001), and zooplankton (Gorokhova 2005). RNAlater has consequently gained popularity as a preservation method for nucleic acid analyses (e.g., Harlow et al 2006;Höök et al 2008;MacLean et al 2008).…”
mentioning
confidence: 99%